Implementation of E-Report Cards in Summative Assessment Management to Improve the Effectiveness of Reporting Student Learning Outcomes - Kirmadi, Yudi; Iskandar, Yogi; Subandi, Ika; Ningsih, Syafitri; Wasitoh, Evi; Suryaman, Maman (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2026)
This study analyzes the implementation of e-Reports in managing summative assessments and its contribution to improving the effectiveness of reporting elementary school student learning outcomes. The main focus is how e-Reports overcomes the weaknesses of the manual system, such as late grade announcements, high recapitulation errors, and limited access for parents. A mixed methods approach was used, combining a systematic literature review of the literature, national policies, and previous research, as well as a descriptive questionnaire survey of 35 teachers from eight educational units. Data analysis followed the Miles et al. (1994) model through data reduction, presentation, and conclusion drawing. The results indicate high effectiveness of e-Reports in time efficiency (score 4.45; recapitulation process from 7 days to <2 days), data accuracy (85% reduction in errors; 98% reliability), and reporting transparency (score 4.55) via a real-time digital dashboard. Teacher satisfaction was very high (4.60), although challenges in digital literacy (3.25) and ICT infrastructure (3.10) remain. Implications include strengthening teacher literacy, improving infrastructure, and integrating e-Reports with Education Reports for data-driven planning. Further research recommendations include a 2–3-year longitudinal study to assess the impact on learning quality and equity.